PENGARUH UKURAN PERUSAHAAN DAN MOTIVASI SOSIAL TERHADAP SUSTAINABILITY REPORT PADA PERUSAHAAN MANUFAKTUR SUB SEKTOR MAKANAN DAN MINUMAN YANG TERDAFTAR DI BEI TAHUN 2019-2022 - Nofita, Amda Rizqi Dwi; Yanti, Yanti; Puspitasari, Meliana (Pusat Penelitian dan Pengabdian bagi Masyarakat Politeknik Negeri Tanah Laut, 2024)
Sustainability reports are one of the most important company or organizational media. The purpose of this sustainability report is to inform the organization's financial performance as well as the size of the company. This determines the size of a company and determines the openness that can be implemented by a company. The next factor that influences the sustainability report in a company is the social motivation of company management. This research aims to assess the influence of company size and social motivation on sustainability reporting. The research method used is a quantitative method sourced from secondary data. Purposive sampling is the method used in the sampling process. The data processing technique in this research uses SmartPLS software version 3.0. The results of this research show that company size and social motivation have a significant effect on sustainability reports Keywords: Company Size, Social Motivation, Sustainability Reporting